On Achieving Strategic Goals and Ensuring the Security of Modern Russia - S. V. Kazantsev (Мир новой экономики)
The strategic objectives of the subject (a person, a group of individuals, an estate, a class, a nation, a community, a state, groups of states, a society) are determined mainly by the conditions in which the subject is located. It includes its specifications (including traditions, worldview, level of development, and available knowledge) by its capabilities and opportunities. Changing even one of the listed factors can cause a change in goals. The paper presents the results of a study of the movement towards achieving vital goals that society sets for the long term: society’s strategic goals. The goal of society in this study the author understood as a specific image (representation) of the result formed by society, which it strives to achieve. The author assessed the speed and nature of the movement towards achieving the constituent components of the strategic goals of the Russian Federation — preserving the nation and increasing the economic power of the country. Statistical data of the World Bank and the Federal State Statistics Service of the Russian Federation from 1992 to 2020 served as initial information for calculations. The calculations performed showed that the movement towards achieving the set goals was of an oscillatory nature, and the amplitude of fluctuations in time tended to decrease. The latter indicates a slowdown in the speed of approaching the set goals.